Main biomarkers of renal injury in anabolic users: an integrative literature review (Research, Society and Development, 2022)
Introduction: The habit of performing physical exercises contributes to a healthy lifestyle. Many bodybuilding practitioners and other sports opt for the use of synthetic anabolic steroids to improve physical strength and muscle hypertrophy. However, these steroids are harmful to the user's health and are related to kidney damage, which can be detected by measuring biomarkers. Objective: To identify the main biomarkers that signal renal damage due to exogenous anabolic steroid abuse. Methodology: SciELO, PubMED, and LILACS databases were searched for the keywords "anabolic steroids", "biomarkers", "acute kidney injury", and "kidneys", as well as the English versions "anabolic steroids", "biomarkers", "acute kidney injury", and "kidney", together with the Boolean term AND. We included articles published in the last 5 years, in English, Portuguese, and/or Spanish, about changes in renal biomarkers caused by anabolic steroids. Duplicate, incomplete or paid articles, studies that did not deal with renal biomarkers or that escaped the topic were excluded. Results: The sample consisted of 15 articles, with the majority being case reports and literature reviews. The anabolic steroids most described in the literature were testosterone and stanozolol, called AAS when used together. Renal lesions were closely intertwined with hepatic dysfunction, and the main renal biomarkers altered were creatinine and urea. Final Considerations: Although creatinine and urea are the most commonly used biomarkers to detect kidney injury, they are not highly sensitive. Therefore, new biomarkers are being studied in order to improve the diagnosis and prognosis of renal injuries.